PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GEOGEBRA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA SMP NEGERI 2 PEMATANG SIANTAR - Rianita Simamora; Yoel Octobe Purba (Universitas Islam Sumatera Utara, 2026)
This study aims to describe the level of validity of the learning media, to describe the level of teacher mastery and student engagement, and to describe the responses of teachers and students to the development of learning media using Geogebra on the topic of the Cartesian plane at SMP Negeri 2 Pematang Siantar, with a sample size of 30 students. The type of research used is research and development based on the ADDIE model, which consists of Analysis, Design, Development, Implementation and Evaluation. Based on the results of the research conducted, it can be stated that the study has successfully developed a digital media product; the data found indicates that the resulting media meets the criteria for validity, reliability, effectiveness and efficiency.